2021
DOI: 10.1002/ejic.202100456
|View full text |Cite
|
Sign up to set email alerts
|

Metallophilic Interactions in Bimetallic Cyclometalated Platinum(II) N‐Heterocyclic Carbene Complexes

Abstract: Platinum(II) complexes with rigid and electron donating ligands are efficient phosphorescent emitters at room temperature. However, the excited‐state lifetimes of these complexes are, in general, relatively long. This problem, which can result in the degradation of the emitter, can be overcome by exploiting the natural tendency of platinum to form metallophilic interactions and aggregates. Herein, we report platinum(II) bimetallic complexes with 100 % quantum yield and at the same time exceptionally short radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
14

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(57 citation statements)
references
References 63 publications
4
39
0
14
Order By: Relevance
“…[15] This is consistent with the observation for related cyclometalated Pt(II) dimers that show an emissive 3 MMLCT [dσ*(Pt 2 )→π*(C^C*)] excited state. [11,12] A redshift in emission λ max of 3-12 nm was observed for 3(C), 4(C), 5, and 6 upon increasing solvent polarity (Figure S11…”
Section: Photophysical Propertiesmentioning
confidence: 99%
See 4 more Smart Citations
“…[15] This is consistent with the observation for related cyclometalated Pt(II) dimers that show an emissive 3 MMLCT [dσ*(Pt 2 )→π*(C^C*)] excited state. [11,12] A redshift in emission λ max of 3-12 nm was observed for 3(C), 4(C), 5, and 6 upon increasing solvent polarity (Figure S11…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…During the preparation of this manuscript, Strassner et al reported the synthesis and photophysical data of 5. [12] In principle, the ditopic bis-µ 2 -formamidinate bridging ligands could adopt multiple structural arrangements with respect to the two [Pt(C^C*)] units, such as forms A, B, and C depicted in Figure 1. In this work, only two of the geometric isomers of [Pt(C^C*)] 2 (N 4 ) (1-4) were obtained.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations